Validation of the Peak Pruritus Numerical Rating Scale as a Patient-Reported Outcome Measure in Prurigo Nodularis - Shawn G. Kwatra; Danielle Rodriguez; Carla Dias-Barbosa; Ismail Budhiarso; Fatoumata Fofana; Margaret Vernon; Sylvie Gabriel; Christophe Piketty; Jorge Puelles (Adis, Springer Healthcare, 2023)
Abstract Introduction Validated patient report tools for quantifying patient experiences of itch in prurigo nodularis (PN) are limited. This study aimed to evaluate the validity of the 11-point peak pruritus numerical rating scale (PP NRS) as a single-item patient-reported outcome (PRO) measure for assessing itch severity in PN. Methods Content validity of the PP NRS was evaluated through qualitative interviews with adults with PN. The PP NRS was then psychometrically evaluated using data from a placebo-controlled trial of nemolizumab in adults with PN, during which patients completed the PP NRS daily. Meaningful within-patient change was estimated from the qualitative interviews and by anchor- and distribution-based analyses of trial data. Results The interview participants (N = 21) all understood the PP NRS and reported itch as their worst symptom overall. The PP NRS showed good test-retest reliability and demonstrated convergent validity and known-groups validity. PP NRS scores improved more in patients classified as "improved" on other clinical outcome measures than in those classified as "worsened/unchanged". Triangulation of the different estimates identified a 2- to 5-point decrease in PP NRS score as a meaningful within-patient change threshold. Conclusion The PP NRS is a content-valid and reliable PRO measure for quantifying itch severity in adults with PN in clinical trials. Trial Registration Number NCT03181503.